Correlations between expression levels of thymidylate synthase, thymidine phosphorylase and dihydropyrimidine dehydrogenase, and efficacy of 5-fluorouracil-based chemotherapy for advanced colorectal cancer - Bai, Wenqi (Int J Clin Exp Pathol, 2015)
The efficacy of 5-fluorouracil (5-FU)-based chemotherapy for colorectal cancer (CRC) widely varies among patients; therefore, it is difficult to accurately predict chemotherapeutic responses. Some recent studies have found that key enzymes in the various metabolic pathways activated by 5-FU present potential predictors of treatment outcome. Of these enzymes, thymidylate synthase (TS), thymidine phosphorylase (TP), and dihydropyrimidine dehydrogenase (DPD) are known to play important roles in the efficacy of therapeutic agents. Here, we measured expression levels of TS, TP, and DPD in formalin-fixed, paraffin-embedded, CRC specimens and paracancerous tissue with normal mucosa by immunohistochemical and fluorescence real-time quantitative polymerase chain reaction techniques. We found no significant differences in TS, TP, and DPD expression levels between CRC specimens and paracancerous tissues (P > 0.05), although overall survival and the chemotherapeutic effect were relatively poor in CRC patients with relatively high expression levels of TS, TP, and DPD, as compared to those with comparatively low expression levels (P < 0.05). Therefore, TS, TP, and DPD mRNA levels appear to be suitable indicators of the efficacy of 5-FU-based chemotherapy and prognosis of CRC.